Hops compounds modulatory effects and 6-prenylnaringenin dual mode of action on GABAA receptors - Ali Y.Benkherouf; Nora Logrén; Tamara Somborac; Maaria Kortesniemi; Sanna L. Soini; Baoru Yang; Outi M.H.Salo-Ahen; Oskar Laaksonen; Mikko Uusi-Oukari (Elsevier, 2022)
Hops (Humulus lupulus L.), a major component of beer, contain potentially neuroactive compounds that made it useful in traditional medicine as a sleeping aid. The present study aims to investigate the individual components in hops acting as allosteric modulators in GABAA receptors and bring further insight into the mode of action behind the sedative properties of hops. GABA-potentiating effects were measured using [3H]ethynylbicycloorthobenzoate (EBOB) radioligand binding assay in native GABAA receptors. Flumazenil sensitivity of GABA-potentiating effects, [3H]Ro 15–4513, and [3H]flunitrazepam binding assays were used to examine the binding to the classical benzodiazepines site. Humulone (alpha acid) and 6-prenylnaringenin (prenylflavonoid) were the most potent compounds displaying a modulatory activity at low micromolar concentrations. Humulone and 6-prenylnaringenin potentiated GABA-induced displacement of [3H]EBOB binding in a concentration-dependent manner where the IC50 values for this potentiation in native GABAA receptors were 3.2 μM and 3.7 μM, respectively. Flumazenil had no significant effects on humulone- or 6-prenylnaringenin-induced displacement of [3H]EBOB binding. [3H]Ro 15–4513 and [3H]flunitrazepam displacements were only minor with humulone but surprisingly prominent with 6-prenylnaringenin despite its flumazenil-insensitive modulatory activity. Thus, we applied molecular docking methods to investigate putative binding sites and poses of 6-prenylnaringenin at the GABAA receptor α1β2γ2 isoform. Radioligand binding and docking results suggest a dual mode of action by 6-prenylnaringenin on GABAA receptors where it may act as a positive allosteric modulator at α+β- binding interface as well as a null modulator at the flumazenil-sensitive α+γ2- binding interface.